DEVELOPMENT OF A REAL-TIME PETROLEUM PRODUCTS ADULTERATION DETECTOR FOR LIQUID AND PARTICULATE CONTAMINANTS (2022)
Adulteration of petroleum products with the resultant safety, health, environmental and economic impact on the end-users is a challenge in Nigeria and many developing countries. The current commonly used techniques by regulatory agencies and some end-users for quality assurance of the petroleum products are time-consuming and expensive. The development and use of real-time adulterated petroleum products detector in Nigeria will therefore alleviate these problems. This study was therefore designed to develop a device for real-time detection of petroleum products adulterated with liquid and particulate contaminants. Pure samples of Premium Motor Spirit (PMS), Automotive Gas oil (AGO) and Dual Purpose Kerosene (DPK) were collected from some major petroleum products marketers. Samples of distilled water, naphtha, commercial ethanol, pure and used commercial lubricating oil, and High Pour Fuel Oil (HPFO) were also obtained and used as liquid contaminants; while sawdust, ash and fine-grain sand were used as solid particulates. At temperatures 23:1:28oC, binary mixtures of the products mixed with liquid contaminants were prepared (100:0, 95:5, 85:15, 75:25, 70:30, 65:35 … 15:85, 5:95,0:100 v/v). Likewise, a fixed volume of pure petroleum products was mixed with varying quantity of solid particulates (0, 2, 4, 6, 8, 10 g). The specific Gravity (SG) and Interfacial Tension (IFT) of the pure samples, binary mixtures were determined according to ASTM D1298 and D971 standards, respectively. These physiochemical properties (SG and IFT) of pure and contaminated fuel samples were used to develop a mathematical model. The model was then simulated into a microcontroller-based detector. A microcontroller of PIC16f876 microchip with multiple input/output pins and a load cell sensor with real-time response was used. The microcontroller takes the reading of the weight of liquid from the sensor to get the SG and IFT of the liquid in real-time. Values of SG and IFT of pure and contaminated samples of petroleum products were obtained using the developed adulteration detector and compared with laboratory measurements and those obtained using Kay’s mixing rule. Data were analysed using ANOVA at α 0.05. The SG and IFT (dynes/cm) of the pure samples were (PMS) 0.833, 47.0; (AGO) 0.812, 28.0; (DPK) 0.803, 25.0, for liquid contaminants ranged from (PMS) 0.853-0.890, 44.6-25.0; (AGO) 0.807-0.804, 46.2-29.5; (DPK) 0.811-0.947, 46.4-38.0 and for solid contaminants ranged from (PMS) 0.887-0.910, 47.8-27.2; (AGO) 0.884-0.887, 29.2-30.0; (DPK) 0.817-0.857, 25.8-32.8, respectively. The SG and IFT from Kay’s mixing rule ranged from (PMS) 0.851-0.900, 48.4-25.6; (AGO) 0.850-0.871, 40.1-35.4; (DPK) 0.864-0.881, 42.4-36.4, respectively. Adulteration of products was detected at 20.0-30.0% by volume and 10.0-20.0% by mass of contamination, respectively. The designed adulteration detector responded to the sample in real-time of 3-5s, displayed GREEN and RED for pure and adulterated samples, respectively, with their numerical SG values within ±0.01% of actual measurements. There was no significant difference between the actual and detected SG and IFT of the adulterated samples. A device that detects petroleum products adulteration in real-time and ambient temperature was developed. The method can be adapted to real-time evaluation of similar binary mixtures.